The Effect Of Several Macroeconomic Variables On Stock Returns Of Manufacturing Companies in Indonesia - Desak Made Sukarnasih; Desak Ayu Sriary Bhegawati (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of macroeconomic factors consisting of inflation, rupiah exchange rate, and interest rates on stock returns of manufacturing companies listed on the Indonesia Stock Exchange during the period 2021-2023. The research method uses a quantitative approach with multiple linear regression analysis. The research sample consists of manufacturing companies listed on IDX during the research period, selected using purposive sampling method. The results show that among the three macroeconomic factors studied, only the rupiah exchange rate has a significant influence on the stock returns of manufacturing companies. This is due to the characteristics of the manufacturing industry which has a high dependence on imported raw materials, so that exchange rate fluctuations directly affect the company's financial performance and stock returns. Meanwhile, inflation and interest rates did not show a significant effect on stock returns of manufacturing companies during the study period.